The potential of pijuayo (Bactris gasipaes) as a new ingredient in meat and fish products - Rios-Mera, Juan Darío (2025)
The association of processed food consumption with health problems has sparked interest among consumers and the food industry in the production of healthier and more sustainable foods. Processed meats, which are made from the skeletal muscle of edible animal species, have unfavorable characteristics due to the incorporation of ingredients and synthetic additives associated with the occurrence of diseases and allergies. In this context, this review presents the pijuayo as a healthy and sustainable alternative in the formulation of meat and fish products. The nutritional benefits of this Amazonian resource are described, as well as its uses reported in the literature. The pulp, peel, stem, and oil extracts of pijuayo have been used to replace animal fat and to act as extenders and colorants in processed meats. The benefits include the enhance of sensory characteristics and acceptability related to texture and flavor, as well as the potential to reduce lipid oxidation and partially replace nitrites as a colorant. However, further studies are still needed to evaluate the effect of pijuayo on processed meats from a holistic perspective, including nutritional aspects and health effects.